2016
DOI: 10.1002/etc.3251
|View full text |Cite
|
Sign up to set email alerts
|

Competing mechanisms for perfluoroalkyl acid accumulation in plants revealed using an Arabidopsis model system

Abstract: Perfluoroalkyl acids (PFAAs) bioaccumulate in plants, presenting a human exposure route if present in irrigation water. Curiously, accumulation of PFAAs in plant tissues is greatest for both the short-chain and long-chain PFAAs, generating a U-shaped relationship with chain length. In the present study, the authors decouple competing mechanisms of PFAA accumulation using a hydroponic model plant system (Arabidopsis thaliana) exposed to a suite of 10 PFAAs to determine uptake, depuration, and translocation kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 35 publications
7
33
0
Order By: Relevance
“…These may explain the lower transfer efficiency from root to shoot of 6:2 Cl-PFESA relative to PFOS. Since 6:2 FTS has a relatively low molecular weight and hydrophobicity (log K ow < 4), 49 its translocation within plants was preferable.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These may explain the lower transfer efficiency from root to shoot of 6:2 Cl-PFESA relative to PFOS. Since 6:2 FTS has a relatively low molecular weight and hydrophobicity (log K ow < 4), 49 its translocation within plants was preferable.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Pharmacokinetic one-compartment models combined with first-order kinetics have been successfully used to describe the process of organic chemical uptake by plants from water (Muller et al, 2016;Zhou et al, 2020). In this study, the root uptake kinetics of 11 pesticides were fitted with a first-order 1-compartment kinetic model.…”
Section: Uptake Kineticsmentioning
confidence: 99%
“…Recent studies have shown that the biological accumulation of PFASs followed a U-type trend. The lowest hydrophobicity (e.g., PFBA and PFPeA) and the maximum hydrophobic species (e.g., PFNA and PFDA) presented the greatest absorb efficiency [66]. Another study on the uptake and distribution of PFASs in maize showed that plant adsorption and distribution of PFASs were dependent on chain length, functional groups, and plant tissue.…”
Section: Bioremediation Techniquesmentioning
confidence: 99%